Peak treadmill running velocity during VO2max test predicts running performance - Noakes, T. D.; Myburgh, K. H.; Schall, R. (Journal of Sports Sciences, 1990)
Marathon runners (N = 20) and ultra-marathoners (N = 23) were tested for VO2max, peak treadmill running velocity, velocity at lactate turnpoint, and VO2 at 16 km/h using an incremental (1 min) treadmill test. Conclusion: There may be no unique physiological characteristics that distinguish elite long-distance (10 km or longer) runners as is often promoted. Other factors determine success in high level sports among exclusive groups of superior athletes. Implication: Running performance is the best predictor of running capability in elite long-distance runners. Physiological laboratory testing gives less information than does actual performance. Even the fastest speed of running on the treadmill is a better predictor than any physiological measure. This suggests that for at least endurance-dominated sports, actual performances in a variety of performance-specific situations will give more useful information than that which can be obtained in any physiology laboratory test.